Inter-professional Perinatal Simulation training: A valuable educational model to improve competencies amongst student midwives in Brussels, Belgium. (February 2016) - Vermeulen, Joeri; Beeckman, Katrien; De Clercq, Gerlinde; Vandelannoote, Isabelle; Gucciardo, Léonardo; Laubach, Monika; Swinnen, Eva
Abstract: Simulation training is a powerful and evidence-based teaching method for students and healthcare professionals. The described educational model of Inter-professional Perinatal Simulation training is the result of a collaborative project with the Erasmus University College Brussels, the Medical School of the Vrije Universiteit Brussel (VUB) and the University Hospital Brussels. This model enhances student midwives to acquire competencies in all fields of midwifery according to national and European legislation and to the International Confederation of Midwives Global Standards for Midwifery Education. In our educational program, simulation training enhanced the achievement of decision-making and inter-professional communication competences.